Refined prediction of vertical gradient of gravity at Etna volcano gravity network (Italy) - ZAHOREC, Pavol; PAPČO, Juraj; VAJDA, Peter; GRECO, Filippo; CANTARERO, Massimo; CARBONE, Daniele (Contributions to Geophysics and Geodesy, 2018)
Predicted values of the vertical gradient of gravity (VGG) on benchmarks of Etna’s monitoring system, based on calculation of the topographic contribution to the theoretical free-air gradient, are compared with VGG values observed in situ. The verification campaign indicated that improvements are required when predicting the VGGs at such networks. Our work identified the following factors to be resolved: (a) accuracy of the benchmark position; (b) gravitational effect of buildings and roadside walls adjacent to benchmarks; (c) accuracy of the digital elevation model (DEM) in the proximity of benchmarks. Benchmark positions were refined using precise geodetic methods. The gravitational effects of the benchmark-adjacent walls and buildings were modeled and accounted for in the prediction. New high-resolution DEMs were produced in the innermost zone at some benchmarks based on drone-flown photogrammetry to improve the VGG prediction at those benchmarks. The three described refinements in the VGG prediction improved the match between predicted and in situ observed VGGs at the network considerably. The standard deviation of differences between the measured and predicted VGG values decreased from 36 to 13 μGal/m.